A feasibility study on use of banana fabrics in footwear production as upper material (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
The purpose of this research is to evaluate the physical, comfort, structural and thermal properties of banana fabrics fortheir suitable use with cow nubuck and goat nubuck leather in footwear applications. It is observed that all these fabrics havemechanical properties comparable to those of cow nubuck and goat nubuck leather. The tensile strength of the banana fabricis sufficiently higher than that of cow nubuck and goat nubuck leather. Cow nubuck leather, on the other hand, outperformsall other fabrics in terms of percentage elongation. Scanning electron microscopic examination gives solid proof of thebanana fabrics’ distinctive fibre pattern in each fibre bundle (yarn) as well as their composition. The banana fabric hasgreater thermal stability than cow nubuck leather. The results of this investigation indicate that the chosen banana fabricscan be used to create footwear.